2017
DOI: 10.1016/j.ydbio.2016.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Porcupine-dependent Wnt signaling controls stromal proliferation and endometrial gland maintenance through the action of distinct WNTs

Abstract: Wnt signaling has been shown to be important in orchestrating proper development of the female reproductive tract. In the uterus, six members of the Wnt family are expressed in the neonatal endometrium and deletion of individual Wnt genes often leads to similar phenotypes, suggesting an interaction of these genes in uterine development and function. Furthermore, Wnts may have complementary functions, which could mask the identification of their individual functional role in single gene deletions. To circumvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…However, we were unable to find any evidence of enhanced CTNNB1 expression. Consistent with this, the phenotypic changes observed in the reproductive tracts of Lats1 flox/flox ; Lats2 flox/flox ; Amhr2 cre/+ mice appeared completely unrelated to those in any previously reported mouse models in which WNT signaling was altered in the Müllerian duct (Dunlap et al, 2011;Farah et al, 2017;Franco et al, 2011;Mericskay et al, 2004;Prunskaite-Hyyrylainen et al, 2016;St-Jean et al, 2019;Vainio et al, 1999). Inactivation of Hippo in Lats1 flox/flox ; Lats2 flox/flox ; Amhr2 cre/+ mice did, however, clearly result in the activation of the canonical Hippo effectors YAP and TAZ, as shown by their increased expression, along with that of their transcriptional target genes.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, we were unable to find any evidence of enhanced CTNNB1 expression. Consistent with this, the phenotypic changes observed in the reproductive tracts of Lats1 flox/flox ; Lats2 flox/flox ; Amhr2 cre/+ mice appeared completely unrelated to those in any previously reported mouse models in which WNT signaling was altered in the Müllerian duct (Dunlap et al, 2011;Farah et al, 2017;Franco et al, 2011;Mericskay et al, 2004;Prunskaite-Hyyrylainen et al, 2016;St-Jean et al, 2019;Vainio et al, 1999). Inactivation of Hippo in Lats1 flox/flox ; Lats2 flox/flox ; Amhr2 cre/+ mice did, however, clearly result in the activation of the canonical Hippo effectors YAP and TAZ, as shown by their increased expression, along with that of their transcriptional target genes.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, deletion of the Wnt7a gene results in a partially posteriorized female reproductive tract, with uterus-like oviducts and a uterus with histological characteristics of the vagina (Dunlap et al, 2011). Wnt4, Wnt5a and Wnt7a have also all been implicated in uterine gland formation (Dunlap et al, 2011;Farah et al, 2017;Franco et al, 2011;Mericskay et al, 2004;St-Jean et al, 2019). Although the signaling processes whereby WNT ligands direct the development of the female reproductive tract are poorly understood, the canonical WNT signaling effector β-catenin (CTNNB1) is believed to play an important role, largely based on phenotypic abnormalities observed in Ctnnb1 conditional knockout models that mimic to some extent those observed in knockout models of specific WNT genes (Deutscher and Hung-Chang Yao, 2007;Hernandez Gifford et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“… 42 Studies also manifested that Wnt/ β -catenin signaling pathway was involved in embryo implantation, stromal proliferation, deciduation and gland maintenance. 43 , 44 Monhamed et al 45 reported that Wnt/ β -catenin signaling was first transiently activated in the uterine luminal epithelium at the prospective site of implantation in mouse. Here, we found that decreased LeY by miR-200c mimics transfection or LeY antibody blocking on CD44 inactivated Wnt/ β -catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a variety of genetically engineered mouse models have helped us identify many crucial genes contributing to uterine adenogenesis, including Foxa2, Wnt7a, Lgr4 and Dlx5/6. 4,6,[8][9][10][11][12][13] However, potential contribution of epigenetic regulators during uterine adenogenesis remains mysterious and barely explored yet.…”
mentioning
confidence: 99%